Rituximab in the Management of a Child with Pemphigus Vulgaris: Case Study - Nikolay N. Murashkin; Leonid A. Opryatin; Anastasiya A. Vasilenko; Eduard T. Ambarchian; Roman V. Epishev; Alexander I. Materikin; Roman A. Ivanov (Вопросы современной педиатрии)
Background. Pemphigus vulgaris is an autoimmune bullous dermatosis. Its management generally involves lifelong administration of maintenance dose of systemic glucocorticosteroids, that leading to serious adverse effects especially in children.Clinical case description. Patient is the 16 years old boy with severe course of pemphigus vulgaris. The diagnosis was confirmed by the results of cell smear study from fresh erosions (> 50 acantholytic cells were revealed), histological examination of the skin biopsy from the lesion with the vesicle element (suprabasal vesicle was localized in the center, it included fibrin, neutrophil granulocytes, and acantholytic cells), skin biopsy from the area near the lesion (visually healthy skin), via direct immunofluorescence methods (IgG deposition was detected on keratinocytes’ surface throughout the epidermis), and enzyme-linked immunosorbent assay (desmoglein 1 IgG autoantibodies — 121 U/mL (reference value < 20 U/mL) and desmoglein 3 — > 200 U/mL (reference value < 20 U/mL)). Genetically engineered biologic drug, rituximab, and systemic glucocorticosteroid, methylprednisolone, were prescribed as first-line therapy with gradual dose reduction to permanent discontinuation in 8 months. Complete remission maintained after the completion of therapy course and discontinuation of systemic glucocorticosteroid.Conclusion. Combined therapy with systemic glucocorticosteroids and rituximab can be considered as first-line therapy in pediatric patients with pemphigus vulgaris due to relatively low risk of recurrence after rather rapid and complete drugs’ discontinuation.